Measuring Commitment and its Impact on Sustainable Performance: A Case Study on Hajee Mohammad Danesh Science and Technology University, Bangladesh (Global Journal of Management and Business Research, 2014)
Faculty members' of any University are playing a crucial role for students and the administration of University should be aware of the importance of faculty members' commitment and its role in motivating them for sustaining their performance. The purpose of this study was to identify the impact of faculty members' commitment on sustained performance in University sector of Bangladesh. Both primary and secondary data has been used for the study. Primary data were collected through structured questionnaires and secondary data were used to identify the commitment related problems of the faculty members' of University and collected from related journals, books, websites. In this study Satisfaction, Affective Commitment, Continuance Commitment & Normative Commitment have been used as independent variables and Sustained performance as the dependent variable. The findings of the study indicated that normative commitment is significantly related to sustained performance, continuance commitment is negatively related and affective commitment, satisfaction have no relation with sustained performance. The finding reveals that there exists a significant relation between satisfaction and Affective Commitment, Continuance Commitment, Normative Commitment. The study suggests that the administration should be working towards the faculty members' satisfaction and organizational commitment.
Keywords: satisfaction; affective commitment; continuance commitment; normative commitment; sustained performance